Institutional learning and change in the CGIAR: summary record of the workshop held at IFPRI, Washington, DC, February 4-6, 2003 - Mackay, Ronald; Horton, Douglas (International Food Policy Research Institute, 2003)
This report summarizes the papers presented and the discussions that took place at the workshop on Institutional Learning and Change in the CGIAR held at the International Food Policy Research Institute (IFPRI) in Washington, D.C. from February 4–6, 2003. The workshop brought to together researchers, donors, and practitioners to develop a strategy for promoting a culture and set of practices conducive to institutional learning and change (ILAC) within the Consultative Group on International Agricultural Research (CGIAR) system.